1990
DOI: 10.1111/j.1468-2958.1990.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Theories of Marriage and Evaluations of Marriage on Television

Abstract: This study integrated social-cognitive and interpersonal frameworks in the mass communication setting. Although television presents afairly consistent view of marriage as corrventionaland happy, we proposed that collegestudents'maritalschemata, or implicit theories about niarriage, would influence their evaluations of television couples'marital satisfaction. Collegestudents (N = 358) completed two waues ofquestionnaires that used Fitzputrick's (1988) Relational Dimensions Instrument to assess marital schemata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…One other study (Perse, Pavitt, & Burggraf, 1990) did obtain an interaction of own and television couple type for their one dependent variable, perceived marital satisfaction. However, the televised couples rated were self-selected rather than experimentally provided, rendering interpretation of the interaction uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…One other study (Perse, Pavitt, & Burggraf, 1990) did obtain an interaction of own and television couple type for their one dependent variable, perceived marital satisfaction. However, the televised couples rated were self-selected rather than experimentally provided, rendering interpretation of the interaction uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, television is probably more conservative in its presentation of family than in any other area. Much of the research indicates that television presents an image of the family as traditional and happy (Gerbner, Gross, Morgan, & Signorielli, 1980;Perse, Pavitt, & Burggraf, 1990;Signorielli, 1982;Skill, Robinson, & Wallace, 1987), demonstrating more affiliative behaviors than confrontational or withdrawing behaviors (Greenberg, Hines, Buerkel-Rothfuss, & Atkin, 1980;Heintz, 1992). Still, the modern sitcom is not all sweetness; rather, it is full of ribald sex jokes and crude language.…”
Section: The Academic Debatementioning
confidence: 99%
“…In studies on the effects of television family portrayals, the results are not always so positive but may be traditional. Heavy viewing adolescents perceived being single as negative (Morgan & Harr-Mazer, 1980, in Perse et al, 1990 and expressed interest in getting married at a younger age (Gerbner et al, 1980). Buerkel-Rothfuss and Mayes (1981) showed that grammar school children who were exposed to heavy doses of soap operas changed their perceptions of the number of happy marriages, divorces, extramarital affairs, and of desirable careers.…”
Section: The Academic Debatementioning
confidence: 99%
“…Hawkins, Pingree, Fitzpatrick, Thompson, and Bauman (1991) focused on the ways in which individuals applied their schemata about communication in marriage to both mediated couples (clips from movies) and nonmediated couples. Perse, Pavin, and Burggraf's (1990) study of perceptions of marriage was prompted by Berger and Chaffee's (1988) suggestion that researchers study cognition to integrate mass and interpersonal communication. They found that individuals' existing perceptions of marriage influenced their evaluations of marriage satisfaction for couples portrayed on television.…”
Section: Contributions To Synthesis Scholarship: Human Communication mentioning
confidence: 99%